Sharing history : Arab World - Europe - Museum With No Frontiers (2015)
[Dt.:] Das vom Museum with no Frontiers initiierte Projekt untersucht die Beziehung der arabischen Welt und Europa im 19. Jahrhundert. - [Engl.:] The project initiated by MWNF is the first attempt to specifically address Arab–Ottoman–European history in a way that includes all parties.